Pengaruh Kombinasi Hidroterapi dan Inhalasi Aromaterapi Jasmine terhadap Penurunan Nyeri Pada Ibu Bersalin Kala I di Rumah Sakit Bhakti Mulia Tahun 2024 - Titin Suprehaten; Amalia Indah Puspitasari (Jurnal Ners, 2025)
As many as 91.9% of women experience pain during the first stage of labor. Pain that cannot be managed properly can lead to prolonged labor which is a direct cause of labor complications. This can result in the death of the mother and baby because the mother's breathing and pulse rate increase, consequently disrupting the flow of blood and oxygen to the placenta. Labor pain can be managed pharmacologically and non-pharmacologically. Nonpharmacological therapies are considered safer and more comfortable to be given to first-time laboring mothers. These include hydrotherapy with warm water and the use of jasmine aromatherapy. Warm compresses on painful areas and the content of compounds in jasmine aromatherapy such as linalool and linalyl acetate have analgesic effects that are beneficial in overcoming pain. To determine the effect of combined hydrotherapy and jasmine aromatherapy inhalation on reducing pain intensity.The sampling of this study used a quasy experimental method with a one group pretest and posttest research design. The sample of this study was 37 laboring mothers. Bivariate analysis using Wilcoxon test. The results of this study The results of statistical tests obtained before being given action the majority of pain in respondents was severe pain as many as 27 respondents (73%), and after being given action the majority of respondents were in the mild pain category as many as 19 respondents (51.4%). There is a difference in the average value before the action of 7.27 and the average after the action of 3.51 with a p value of 0.000 where (p <0.05) so that it can be concluded that there is a significant effect of the combination of hydrotherapy and jasmine aromatherapy inhalation on reducing the intensity of pain in laboring mothers during stage I at Bhakti Mulia Hospital in 2024. This confirms that the combination of hydrotherapy and jasmine aromatherapy inhalation does have a real effect in reducing the intensity of pain in laboring women.